A numerical study on the three-dimensional natural convection with a cylinder in a long rectangular enclosure. Part II: Inclination angle effect of the elliptical cylinder. (March 2019) - Seo, Young Min; Ha, Man Yeong; Park, Yong Gap
Highlights: Three-dimensional numerical simulations were conducted for the natural convection. The Immersed Boundary Method was used, based on the Finite Volume Method. The effect of inclination angle of the elliptical cylinder was investigated. The flow and thermal fields and the three-dimensionality were investigated. The effects of inclination angle on the heat transfer characteristics are highlighted. Abstract: This study conducted three-dimensional numerical simulations of the natural convection in a cold, long, rectangular enclosure containing a hot elliptical cylinder. The immersed boundary method (IBM) was used to capture the virtual wall boundary of the inner cylinder based on the finite volume method (FVM). The effect of inclination angles of 0° ≤  ψ  ≤ 90° were analyzed by a visualization technique with various radii of the cylinder at a relatively high Rayleigh number of Ra  = 10 6 . The variation in the flow and thermal structures and the corresponding heat transfer characteristics were investigated in regard to the transition of the flow regime from the steady state to the unsteady state. The heat transfer characteristics from the cylinder surface and enclosure walls were also addressed. As a result, the heat transfer characteristics were improved by the variation in the inclination angle in accordance with the mean radius of the elliptical cylinder.